Understanding Terror : Perspectives for Canadians. - Kassam, Karim-Aly S. (University of Calgary Press, 2010)
Understanding Terror takes a historical approach to consideration of terror through specific examples and its presence in the media in North American society and particularly in Canada. Contributors to the volume include journalists, scholars, and public policy experts, many of whom have dealt with the impact of terror or experienced it first-hand. Their aim is to examine specific events, reflect on how those events might be interpreted, and provide historical context, all the while encouraging the reader to question preconceived characterizations of this highly charged political and cultural issue. --Publisher's description.